Multifocal endometriotic lesions associated with cancer are clonal and carry a high mutation burden. Issue 2 (23rd March 2015) - Anglesio, Michael S; Bashashati, Ali; Wang, Yi Kan; Senz, Janine; Ha, Gavin; Yang, Winnie; Aniba, Mohamed R; Prentice, Leah M; Farahani, Hossein; Li Chang, Hector; Karnezis, Anthony N; Marra, Marco A; et al.
Abstract Endometriosis is a significant risk factor for clear cell and endometrioid ovarian cancers and is often found contiguous with these cancers. Using whole‐genome shotgun sequencing of seven clear cell ovarian carcinomas (CCC) and targeted sequencing in synchronous endometriosis, we have investigated how this carcinoma may evolve from endometriosis. In every case we observed multiple tumour‐associated somatic mutations in at least one concurrent endometriotic lesion. ARID1A and PIK3CA mutations appeared consistently in concurrent endometriosis when present in the primary CCC. In several cases, one or more endometriotic lesions carried the near‐complete complement of somatic mutations present in the index CCC tumour. Ancestral mutations were detected in both tumour‐adjacent and ‐distant endometriotic lesions, regardless of any cytological atypia. These findings provide objective evidence that multifocal benign endometriotic lesions are clonally related and that CCCs arising in these patients progress from endometriotic lesions that may already carry sufficient cancer‐associated mutations to be considered neoplasms themselves, albeit with low malignant potential. We speculate that genomically distinct classes of endometriosis exist and that ovarian endometriosis with high mutational burden represents one class at high risk for malignant transformation. © 2015 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.